Masculinity and male identity - Healey, Justin (Issues in society (Balmain, N.S.W.), 2020)
The status quo of gender-based inequality and discrimination in our society perpetuates the notion that we live in "a man's world". Traditional masculine stereotypes persist in a culture which identifies men as self-reliant, emotionally reticent, focused on work over family, and oversexed. When these beliefs are taken to extreme levels by boys and men, they result in poor relationships, mental health problems and risky behaviours. Rethinking masculinity can help men and boys to move away from narrow masculine ideals and negative role models towards healthier, more diverse approaches to male identity. This book explores what it means to be a "a real man" in Australia, questioning the masculine stereotypes which sustain gender inequality. In addition, the book examines "toxic masculinity", traditional male gender roles, misogyny and attitudes which promote violence and disrespect towards women. It also addresses the impacts of traditional masculine norms on men's health and wellbeing. What does it mean to be a man in a changing world - is there really a crisis in masculinity? How can society - and boys and men as individuals - encourage positive, healthier masculinities?